Efficiency of aviation companies' financing and formation of its investment attractiveness (Journal of Economic Research & Business Administration, 2022)
The article discusses the concept and the choice of sources of financing for the investment activities of aviation companies. The choice of financing instruments for aviation companies, as well as the optimal capital structure, is an important and necessary stage for conducting effective activities aimed at achieving the financial stability of the airline company. Especially the problem of choosing sources of financing becomes relevant in the context of the spread of COVID-19. The object of the article is to study the modeling of investment attractiveness on the example of airlines. Based on the research of investment attractiveness in airlines, recommendations were formulated in the field of investment project evaluation. Scientific and practical significance of the work is that Aviation is one of the fastest growing sectors in the world, combining technology, innovation, entrepreneurship, economic development, infrastructure support, demographic growth, and contribution to globalization. Progress in this sector is impressive in its speed and diversity in nature. Based on the analysis of the investment activity of the Kazakh company, it was revealed that outdated methods of evaluating the effectiveness of investment projects are used and it was proposed to use quantitative risk analysis and break-even assessment of the airline's investment projects for this purpose. In accordance with the research subject, the methods of scientific knowledge, induction, deduction, comparison, statistics, comparability, financial analysis, mathematical modeling, analysis and forecasting were used.Keywords: aviation company, investment, financing, investment company, sources of financing.